Les pays méditerranéens et les échanges internationaux de dattes - Greiner D. (Le palmier dattier dans l'agriculture d'oasis des pays méditerranéens, 1993)
In the Mediterranean region there is an intense date trade, mainly from countries lying on the south coast towards those of the north coast, but the level of trade with other regions in the world present in the trade market is rather modest. This relationship shows the need to look for the new markets for exporters and diversify supply in order to better satisfy the demand of importers. Aiming at placing the Mediterranean countries on the world date market, the author describes the regional structure of trade and presents the recent quantitative evolution of the main markets over the period 1989-1993, based on customs statements of the importing countries.
Journées Internationales d'Elche sur le Palmier Dattier dans L'Agriculture d'Oasis des Pays Méditerranéens, 25-27 Apr 1995, Elche (Spain)